Origin and hidden diversity within the poorly known Galápagos snake radiation (Serpentes: Dipsadidae). Issue 7 (3rd October 2018) - Zaher, Hussam; Yánez-Muñoz, Mario H.; Rodrigues, Miguel T.; Graboski, Roberta; Machado, Fabio A.; Altamirano-Benavides, Marco; Bonatto, Sandro L.; Grazziotin, Felipe G.
Abstract : Galápagos snakes are among the least studied terrestrial vertebrates of the Archipelago. Here, we provide a phylogenetic analysis and a time calibrated tree for the group, based on a sampling of the major populations known to occur in the Archipelago. Our study revealed the presence of two previously unknown species from Santiago and Rábida Islands, and one from Tortuga, Isabela, and Fernandina. We also recognize six additional species of Pseudalsophis in the Galápagos Archipelago ( Pseudalsophis biserialis from San Cristobal, Floreana and adjacent islets; Pseudalsophis hoodensis from Española and adjacent islets; Pseudalsophis dorsalis from Santa Cruz, Baltra, Santa Fé, and adjacent islets; Pseudalsophis occidentalis from Fernandina, Isabela, and Tortuga; Pseudalsophis slevini from Pinzon, and Pseudalsophis steindachneri from Baltra, Santa Cruz and adjacent islets). Our time calibrated tree suggests that the genus Pseudalsophis colonized the Galápagos Archipelago through a single event of oceanic dispersion from the coast of South America that occurred at approximately between 6.9 Ma and 4.4 Ma, near the Miocene/Pliocene boundary.www.zoobank.org/urn:lsid:zoobank.org:pub:2679FD19-01E5-48FE-A0DA-A88FF145DE56